(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Acne vulgaris is a chronic inflammatory disease of the pilosebaceous follicles that is seen primarily in adolescents. Objective: To compare the efficacy of 0.1 % tazarotene cream and 0.05% tretinoin cream in the treatment of mild to moderate acne vulgaris. Methods: A randomized controlled clinical trial was done in the department of Dermatology and Venereology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh. Results: At base line mean number of comedones in group A and group B was 12.77 ± 4.01 and 11.80 ± 3.93 respectively (p=0.350) and at final follow up 4.17 ± 4.02 and 3.47 ± 4.00(p=0.501). At base line mean number ofpapules in group A and group B was 17.30 ± 10.29 and 18.57 ± 13.88 respectively (p=0.690) and at final follow up 7.63 ± 8.08 and 7.73 ± 9.98 (p=0.966). At base line mean number of pustules in group A and group B was 0.50 ± 1.33 and 0.53 ± 1.28 respectively (p=0. 922) and at final follow up 0.07 ± 0.37 and 0.00 (p=0.326). At baseline mean of total acne score was 30.57 ± 13.62 and 30.90 ± 17.17 in group A and B(p=0.934) and at final follow up it was 11.87 ± 12.04 and 11.20 ± 13.85 respectively in group A and B(p=0.846). At 1st follow up 3.3% of both group got excellent response, at 2nd follow up 13.3% of group A and 30.0% of group B got excellent response, and at final follow up 56.7% of group A and 63.3% of group B achieved excellent response. About 73.33% oftretinoin treated patient and 60% oftazarotene treated did not experience any side effects. Conclusion: It can be concluded that 0.1 % tazarotene cream and 0.05% tretinoin cream is individually effective and tolerability of 0.1 % tazarotene is comparable to 0.05% tretinoin in the treatment of mild to moderate acne vulgaris.